Women in the Decision-Making Process - (:unkn) unknown (My University, 2006)
The present study examines women's decision-making within the household, its focus being the power women hold in making day-to-day and strategic decisions. The study focuses on women of two generations and traces changes that have taken place in the status and role of women in an urban low income community (walta), Sri Subuthipura of the Colombo South DS division. The methodology employed in the study includes, collection of empirical data using tools such as in-depth interviews, structured questionnaires and observations. A literature review was. conducted with emphasis on concepts such as power, domination, authority, household, slum, shanty, tenement garden, patriarchy, life cycle, agency and democracy. The study posed the following research problem: "What is the status of women in the decision-making process within the household? The research exposes several factors such as income/resources, education, kinship networks, and political affiliations as several key sources of power that playa pivotal role in decision-making. The burden placed on women within the watta is seen to have intensified due to economic pressures even though the change in the prevailing gender ideology has not taken place at the same pace. Therefore the nexus between the level of empowerment of women in relation to their decisionmaking, as well as the mechanisms that enable and disable women's decisionmaking and empowerment are also explored through the study